DE TJOLOMADOE - Implementasi Penggunaan Kembali Mesin eks Pabrik Gula: - - Purnomo, Agus Dody; Agus, Cecep (BRIN, 2024)
One concept for utilizing heritage buildings is adaptive reuse. It is applied to industrial heritage such as the Colomadu Sugar Factory. For a long time, the building was abandoned and unproductive. This study aims to examine the changes in the function of the ex-sugar factory machines and their role in the interior design of De Tjolomadoe. The research method uses qualitative methods to identify changes in the function of ex-sugar factory machines as current interior elements. The building is brought back to life with a new spirit. Machines from the former sugar factory are maintained and given new functions, which includes: as a supporting element of the sense of place, museum collections, aesthetic elements, and furniture design. The existence of ex-sugar factory machines is an important and unique interior element as well as authentic proof of the glory of the sugar factory.